2022
DOI: 10.1186/s12909-022-03135-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout: exploring the differences between U.S. and international medical graduates

Abstract: Background International medical graduates (IMGs) have less burnout than U. S. medical school graduates (USMGs) during residency training. This study evaluates possible correlates of differences in burnout rates between USMGs and IMGs. Methods We surveyed 375 first-year residents at orientation in June/July 2017. We assessed burnout using the Copenhagen Burnout Inventory (CBI) and used validated scales to measure stress, quality of life (QoL), mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Physicians working longer hours, or those working in primary care had higher odds of emotional exhaustion and feeling depersonalization. IMG status and greater work experience decreased both emotional exhaustion and depersonalization, which is consistent with previous research [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Physicians working longer hours, or those working in primary care had higher odds of emotional exhaustion and feeling depersonalization. IMG status and greater work experience decreased both emotional exhaustion and depersonalization, which is consistent with previous research [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 92%
“…We saw an increase in career satisfaction and time use satisfaction with every additional year in practice. IMG status was associated with higher satisfaction on both measures, which is consistent with previous research [ 17 ].…”
Section: Resultssupporting
confidence: 92%
“…Studies on burnout in medical students have revealed an increased risk in females (Dyrbye, Thomas, Huschka, et al, 2006) and older age groups (Dyrbye, Satele, & West, 2021); however, inconsistencies across studies have been found (Dyrbye, Thomas, Huntington, et al, 2006). Furthermore, differences between countries regarding burnout in medical students have been reported in the existing literature, with higher prevalence in Oceania (Frajerman et al, 2019) and US (St Onge et al, 2022) as compared to other parts of the world. These differences have been related to several country-specific factors, including a wide variation in lifestyle patterns (Lee et al, 2020), family support (Dorrance Hall et al, 2017), and learning environments of medical schools (Bilge et al, 2014; Brown et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 , 15 , 16 The CBI has been applied extensively to physicians. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Despite widespread international use in measuring burnout among physicians, the CBI has been used infrequently to measure burnout among emergency physicians in the United States. 37 , 38 …”
Section: Introductionmentioning
confidence: 99%
“…The CBI has been used to assess varied types of health care personnel in several countries, amassing substantial validity evidence 13–16 . The CBI has been applied extensively to physicians 17–36 . Despite widespread international use in measuring burnout among physicians, the CBI has been used infrequently to measure burnout among emergency physicians in the United States 37–38 …”
Section: Introductionmentioning
confidence: 99%